Electrical stimulation of the Gasserian Ganglion induces structural alterations of calcitonin gene-related peptide-immunoreactive perivascular sensory nerve terminals in the rat cerebral dura mater a possible model of migraine headache - Knyihár-Csillik Erzsébet (NEUROSCIENCE LETTERS, 1995)
Calcitonin gene-related peptide (CGRP)- positive sensory nerve fibers in the rat supratentorial cerebral dura mater are equipped with varicosities and club-like nerve terminals, often attached to the walls of blood vessels. Brief electrical stimulation of the Gasserian ganglion results in significant swelling and increased immunohistochemical staining of ipsilateral perivascular club-like terminals, while long-lasting electrical stimulation induces their disintegration or bursting, resulting in irregular, corroded outlines of terminals and en passant beads. Stimulation-induced morphological alterations of perivascular terminals may represent a structural basis of increased CGRP content in jugular blood which follows electrical stimulation of the Gasserian ganglion and accompanies migraine attacks.